The influence of social anxiety on international students’ learning approach: A case study in Universiti Utara Malaysia - Fitrianti, Erly (2004)
The influx of international students studying abroad has generated numerous studies on cross-cultural problem concerning students' learning approaches. Acknowledging these issues, the objective of this paper is to explore the social anxiety among international students in Universiti Utara Malaysia (UUM) and its influence on their learning approach. A sample of 94 students studying at UUM was randomly selected from population of 124 students. Survey research method with questionnaires using Interaction Anxiousness Scale (Leary & Kowalski, 1987) and Revised Two-Factor Study Process Questionnaire (Biggs, Kember, & Leung, 2001) were chosen to measure the key variables. The findings show that international students studying at UUM have a moderate level of social anxiety and tend to adapt to surface approach in learning, which may associate with their academic performance. The results support some findings on cross cultural learning and refute others. The results also provide implication to policies and programs for supporting internationalization of higher education institution at UUM.